Robot following and escaping for human interfacing using LIDAR-UWB based robot dog - Sng, Aaron Li Wen (Nanyang Technological University, 2023)
Robots are increasingly becoming part of our everyday lives. Various efforts in commercial and research settings have made robots more accessible and capable of enhancing our daily lives with more comfort. Robots as a companion, in particular, is an idea that has been championed in mass media, and is now gradually becoming a reality. The Go1 Robot by Unitree is an example of a robot dog that seeks to bridge the human-robot gap, and will be the main robot of use in this project.